2010
DOI: 10.5194/acp-10-437-2010
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric sub-3 nm particles at high altitudes

Abstract: Abstract. Formation of new atmospheric aerosol particles is known to occur almost all over the world and the importance of these particles to climate and air quality has been recognized. Recently, it was found that atmospheric aerosol particle formation begins at the diameter of around 1.5-2.0 nm and a pool of sub-3 nm atmospheric particles -consisting of both charged and uncharged ones -was observed at the ground level. Here, we report on the first airborne observations of the pool of sub-3 nm neutral atmosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 56 publications
6
76
1
Order By: Relevance
“…The systematic measurements performed within the EUCAARI project support the earlier observations on the contribution of ions to total particle formation in the boreal forest (Laakso et al, 2007b;Kulmala et al, 2007;Gagne et al, 2008;Manninen et al, 2009a) and in other environments (e.g. Mirme et al, 2010;Boulon et al, 2010a, b). The results infer that ion-induced nucleation has a minor contribution to particle formation in the boundary layer in most environments.…”
Section: Discussionsupporting
confidence: 58%
“…The systematic measurements performed within the EUCAARI project support the earlier observations on the contribution of ions to total particle formation in the boreal forest (Laakso et al, 2007b;Kulmala et al, 2007;Gagne et al, 2008;Manninen et al, 2009a) and in other environments (e.g. Mirme et al, 2010;Boulon et al, 2010a, b). The results infer that ion-induced nucleation has a minor contribution to particle formation in the boundary layer in most environments.…”
Section: Discussionsupporting
confidence: 58%
“…The fraction of ion-mediated nucleation is hence higher than at other sites because of the lower neutral nucleation detected at this high altitude site. This finding is conflictual with the results from Mirme et al (2010) who found no sign of an enhance role of ion-induced nucleation toward the tropopause. It is worth mentioning that our J 2 calculation is a higher limit, since 3 nm particles concentrations detected with the SMPS technique were measured to be lower than the 3 nm particles detected from the NAIS.…”
Section: Charged and Neutral Particle Formation Rates And The Role Ofcontrasting
confidence: 57%
“…Some of the results from these flights have already been reported for example by Mirme et al (2010). The French ATR-42 has been equipped with state-of-the-art aerosol and cloud instrumentation.…”
Section: Introductionmentioning
confidence: 99%